Applying Blockchain to the Australian Carbon Market. Issue 2 (14th August 2019) - Hartmann, Sam; Thomas, Sebastian
Abstract : Blockchain is a distributed digital ledger system that establishes transparent contract processes and facilitates secure but trusted business transactions. Policy‐makers around the world are intrigued by the potential of this emerging technology to solve policy problems, including the challenges of the transition away from centralised, linear models of energy generation and consumption towards decentralised and distributed energy systems. Blockchain has also been promoted as a mechanism to transform carbon markets, yet the focus in this area to date has been on using blockchain to create new carbon market schemes. This paper addresses an important research gap by asking how blockchain could be applied to an existing carbon market. To answer this question, the study uses an established design process to develop an Australian carbon market blockchain design. The paper finds that this design could improve the efficiency, equity and effectiveness of the Australian carbon market. This paper makes an important research contribution to carbon market policy development by developing a blockchain design that could improve how an existing carbon market functions, and the findings presented here are relevant to government and industry stakeholders globally.